MENGUKUR EFISIENSI KINERJA KEUANGAN BADAN AMIL ZAKAT NASIONAL (BAZNAS): PENDEKATAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Much. Maftuhul Fahmi; Indah Yuliana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2019)
National Amil Zakat Agency (BAZNAS) as the official amil management body owned by the government has the duty to collect, manage, and distribute zakat on a national scale. BAZNAS itself still has the potential for the collection of zakat that continues to grow, given the accumulation of muzakki funds conducted by BAZNAS is only 1% of GDP (Gross Domestic Product) of Indonesia. The potential possessed by BAZNAS is still constrained by conditions that hinder the process of collecting zakat, so it is necessary to optimize the collection of zakat. One way to optimize BAZNAS performance is to measure its efficiency. Therefore, the purpose of this study is to analyze the efficiency of BAZNAS financial performance. The method used is the Data Envelopment Analysis (DEA) method with the assumption of Constant Return Scale (CRS) and Variable Return Scale (VRS). The measurement of efficiency is processed through the Banxia Frontier Analyst 4.0 software. The BAZNAS research observation period was five years, starting from 2013 to 2017. The research variables used included pooled funds, fixed assets, managed assets, and salary ‘amiline as input variables and channeled funds and operational costs as output variables. The results showed that BAZNAS during the period 2013 to 2017 had reached an efficient value of 100 percent. This is evidenced from the actual value that has reached the target value.